FINANCIAL FEASIBILITY OF NEW PRODUCT VARIANTS CHILDREN’S HEALTHY SNACK BUSINESS: CASE STUDY OF LIL’BITES - Michael Arvan Loekito (Journal of Social and Economics Research, 2024)
Based on data from Indonesian Nutrition Status Survey (SSGI) in 2022, 21.6% of Indonesian children suffer from stunting, and 7.7% experience wasting. Stunting results from chronic malnutrition, causing below-average height, while wasting leads to below-normal weight. These conditions arise from insufficient nutritional intake. Ensuring proper nutrition for children under five requires three regular meals and two snacks daily. Lil'Bites is an FnB start-up that focuses on providing nutritious snacks for children by prioritizing healthy and high-quality raw materials. Currently in the product sales stage, Lil'Bites plans to expand its product flavour variants but has not yet conducted a financial feasibility study for this expansion. This research aims to assess the financial feasibility of developing new snack flavours using a quantitative approach, utilizing company data as primary data and data from similar companies as secondary data. The study will evaluate the payback period, net present value (NPV), and internal rate of return (IRR), and assess risk through sensitivity analysis. The results based on realistic scenario indicate that the Lil'Bites project is financially feasible, resulted with a payback period of 1.7 years, an NPV of IDR166,428,592, and an IRR of 47.96%, which significantly higher than the WACC of 7.39%.